Job Contact Networks and the Ethnic Minorities - Harminder Battu; Paul Seaman; Yves Zenou (The Research Institute of Industrial Economics (IUI), 2004)
This paper examines the job finding methods of different ethnic groups in the UK. The theoretical framework shows that less assimilated ethnic unemployed workers are more likely to use their friends and family as their main method of search but they have less chance of finding a job using this method compared to whites and more assimilated ethnic unemployed workers that use formal job search methods (adverts, employment agencies etc.). Using data from the UK Quarterly Labour Force Survey (QLFS), we test these hypotheses. Our empirical findings are consistent with the theory since they suggest that, though networks are a popular method of finding a job for the ethnic minorities, they are not necessarily the most effective either in terms of gaining employment or in terms of the level of job achieved. However, there are important differences across ethnic groups with the Pakistani and Bangladeshi groups and those born outside the UK (the least assimilated), losing out disproportionately from using personal networks.
Keywords: J15; J64; 330; Job Search; Networks; Social Capital; Ethnic Disadvantage; Arbeitsplatzsuchmodell; Netzwerk; Ethnische Gruppe; Großbritannien; Soziale Beziehungen